2020
DOI: 10.1590/0034-7167-2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

Stress and health risk behaviors among university students

Abstract: Objective: To analyze the level of stress and its relationship with health risk behaviors among university students. Method: Cross-sectional analytical study carried out at a higher education institution in Picos-PI. A total of 377 students were evaluated for socio-demographic and academic variables, stress profile, sleep quality, alcohol use, smoking habits and level of physical activity. The Statistical Package for the Social Sciences (SPSS), version 20.0 was used for data processing and analysis. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
1
7
0
8
Order By: Relevance
“…With respect to the analysis of correlation of time management with the symptom dimension, the result was an inverse relation qualified as low. It is worth mentioning that it has agreed with what was stated by Palacios, Belito, Bernaola and Capcha (2020) as well as with the results given by Oliveira, Silva, Silva, Moura, Araújo and Silva (2020), who pointed out that procrastination influenced on stress in a strong level; they concluded that the generated results could be associated to related factors such as sex, quality of sleep and time at work. Finally, it was possible to demonstrate that there was a direct relationship, at a low level, between time management and the coping dimension.…”
Section: Discussionsupporting
confidence: 89%
“…With respect to the analysis of correlation of time management with the symptom dimension, the result was an inverse relation qualified as low. It is worth mentioning that it has agreed with what was stated by Palacios, Belito, Bernaola and Capcha (2020) as well as with the results given by Oliveira, Silva, Silva, Moura, Araújo and Silva (2020), who pointed out that procrastination influenced on stress in a strong level; they concluded that the generated results could be associated to related factors such as sex, quality of sleep and time at work. Finally, it was possible to demonstrate that there was a direct relationship, at a low level, between time management and the coping dimension.…”
Section: Discussionsupporting
confidence: 89%
“…A review study before the COVID-19 pandemic suggested that university students are vulnerable to stressors related to academic and relational life characteristics, likely to cause psychological distress [ 12 ]. Studies showed worrying percentages of stress among university students in Brazil (52.9% and 68.7%) before the pandemic [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 Other studies have reported a moderate stress level among staff nurses. [17][18][19] A significant correlation was observed between stress and health risk behaviour in this study. Similar findings were observed by Algren et al in a study conducted on 511 staff nurses in Denmark.…”
Section: Correlation Between Stress and Health Risk Behaviourmentioning
confidence: 70%